Pengaruh Model Problem Based Learning (PBL) Berbantuan Multimedia Terhadap Kemampuan Kerjasama Siswa Pada Pembelajaran Tematik di Kelas V SD Negeri Gugus 12 Kota Bengkulu - Regine Pritikasari; Wurjinem Wurjinem; Herman Lusa (JURIDIKDAS, 2021)
This study aims to determine the effect of the use multimedia-based problem-based learning (PBL) models on student collaboration on thematic learning in class V SDN cluster 12 Bengkulu city. This research is quantitative. The research method used is a quasi experimental design with the type of design "the matching only pretest-posttest control group design. The population is SDN cluster 12 Kota Bengkulu. The sampling uses cluster random sampling technique. Subject in this study was class V A SDN 81 Kota Bengkulu as an experimental class and class V B SDN 99 Kota Bengkulu as a control class. The research instrument used in the form of a questionnaire was the ability of students to collaborate given the initial questionnaire and the final questionnaire in the control class and the experimental class. Analysis of data for technique in this research is quantitative analysis using descriptive statistical and inferential statistics namely t-test. From the results of the t-test calculation of the student's final questionnaire value, namely tcount = 2.18 is greater than the value of t table = 2.02. It shows that there are differences in the results of the final questionnaire between the the control class and experimental class. Based on the results of the difference in the final questionnaire value of the experimental class and the control class, it can be concluded that there is a t effect with a 5% scale using multimedia-based problem-based learning (PBL) models towards student collaboration on thematic learning in class V SDN cluster 12 Kota Bengkulu.Keywords: Problem Based Learning Model, Multimedia, Student Collaboration, Thematic Learning